Lithospheric heterogeneities of northeast India and Indo-Burma region: Geodynamic implications - O.P. Mishra (Geosystems and Geoenvironment, 2022)
In order to understand the geodynamical implications of intercontinental subduction, Cenozoic volcanism and ductile sediments in the northeast India and Indo-Burma region, a detailed 3-D P-wave tomography has been conducted using high-quality P-wave phase data recorded by local seismographic network ascribed to different agencies of India. This approach of using local earthquake data recorded by the portable seismographs installed for limited duration also provide an opportunity to adjudge the efficacy of local seismic network, which in turn enrich our understanding of intricate issues of Seismogenesis.P-wave tomographic imaging of lithospheric structure using arrival time data from local earthquakes recorded for the northeast India and Indo-Burma region revealed strong velocity heterogeneities beneath the region. The eastward subduction of the Indian slab beneath the Burmese arc with a dipping plane of intermediate-depth earthquakes has been imaged as high velocity (high-V) zones. Under the Cenozoic volcanic front in Burma, low velocity (low-V) anomalies are imaged. The low-V at shallow crustal layers may correspond to surface geological features, sedimentary materials or the faults associated with trapped fluids or loose pelgic sediments due to episodic tectonic upheavals, dehydration of the subducting Indian slab and serpentinization of the forearc mantle beneath the region, while high-V anomalies in the same depth range possibly indicate the presence of dense crystalline rocks under compressional stress that cause seismicity in the region. The distribution of seismicity is associated with major faults and lineaments associated with the distinct structural heterogeneities. The Bengal basin and the Central Burma Molasse basin exhibit low-V anomalies with very less seismicity due to ductility of the sediments. The low-V associated with the thick piles of sediments in the Bengal (>20 km) and Central Burma Molasse (≤12 km) Basin supported by the conspicuous distribution of low-Bouger gravity anomaly, which may have contributed significantly to major load along with an overthrust load of westward moving Indo-Burma ranges over the Indian lithosphere, which may amplify the stresses already acting on the Indian Plate due to load of the Himalaya, and making the region seismically more vulnerable. The present study is found to be in a good unison to the recent studies conducted in the region using different seismo-geophysical tools to different data set. The study provides valuable information on the lithospheric structures associated with seismogenesis and volcanic activity for the intercontinental regions, elsewhere in the world for our better understanding of geodynamical processes.